Pengaruh Anggaran Berbasis Kinerja dan Sarana Prasarana terhadap Motivasi Serta Dampaknya pada Kinerja Anggota Polri di Kepolisian Resor Tanjung Jabung Barat - M Zahari MS; Yunan Surono; Sufriyanto Sufriyanto (Universitas Batanghari, 2022)
This research was conducted on members of the National Police in the Tanjung Jabung Barat Resort Police, which can be seen from the ability of human resources or officers who are able to complete work related to all activities in the organization and public services, including all activities that exist in the ranks of members of the National Police in the resort police (Polres) Tanjung Jabung Barat. This study uses descriptive and verificative analysis method, descriptive analysis used to describe respondent characteristics and research variables without conducting testing. The verificative analysis is used to determine the magnitude of the influence between independent variables on dependent variables. This study uses census method that is all members of the National Police in the resort police (Polres) Tanjung Jabung Barat, in addition to the data used in this study is the primary data obtained from the results of questionnaires provided and have been filled by each member of the Police in the resort police (Polres) Tanjung Jabung Barat. The data analysis technique used is path analysis, with the help of SPSS software program version 22.0. The results of this study show that the free variables of performance-based budgets and infrastructures positively and significantly affect motivation and have a positive impact on the performance of members of the National Police in the resort police (Polres) Tanjung Jabung Barat, this proves that with the increasing budget-based performance and infrastructure of members of the National Police in the resort police (Polres) Tanjung Jabung Barat, it will also increase the motivation of members that will have an impact on improving the performance of police members in the resort police (Polres) Tanjung Jabung Barat.